2022
DOI: 10.3390/su14127395
|View full text |Cite
|
Sign up to set email alerts
|

The Significance of Digital Marketing in Shaping Ecotourism Behaviour through Destination Image

Abstract: Ecotourism is the most encompassing alternative approach, and it is usually regarded as a panacea capable of combining economic development, environmental protection, and community well-being. Pakistan’s ecotourism industry is relatively new and has significant growth potential, with approximately 6 million domestic and international tourists visiting various northern destinations in 2018. However, as the number of tourists grows, so do the difficulties or obstacles associated with visitor/tourist behaviour, s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
22
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(23 citation statements)
references
References 66 publications
0
22
0
1
Order By: Relevance
“…The loyalty of users is also crucial [56], and many individuals tend to become increasingly interested in the tourist community by reading personal travel evaluations and following Instagram influencers who promote sustainable tourism [6]. This indirect influence seems to accelerate the decision-making process by the followers, as it creates the willingness to choose the same destination [57].…”
Section: Instagram and Influencersmentioning
confidence: 99%
See 2 more Smart Citations
“…The loyalty of users is also crucial [56], and many individuals tend to become increasingly interested in the tourist community by reading personal travel evaluations and following Instagram influencers who promote sustainable tourism [6]. This indirect influence seems to accelerate the decision-making process by the followers, as it creates the willingness to choose the same destination [57].…”
Section: Instagram and Influencersmentioning
confidence: 99%
“…Nowadays, social media platforms have an important role in destination marketing strategies, providing travelers with the opportunity to share their travel experiences in real time [6]. Regarding tourism destinations, Instagram offers a wide range of benefits, especially when financial and marketing resources are limited [7].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Adaptive marketing process makes digital marketing can be implemented in some studies, specifically on ecotourism digital marketing. Some studies which were related to ecotourism digital marketing revealed that the strategy of using digital marketing could boost the number of visitors because it provided various tourist information and was accompanied by some pictures (Khan et al, 2022). That information and pictures are displayed on media-based technology such as social media, blogs, websites, or search engines.…”
Section: Figure 1 Kebun Raya Mangrove Medokan Ayumentioning
confidence: 99%
“…Therefore, the creation of a strong digital branding is essential through digital marketing which includes marketing activities, also branding by using several Web-based media (Amer and Zaheer, 2022; Susila et al , 2022). This digital marketing strategy also applies for destination branding, as the internet is the first choice to seek information about destinations (Khan et al , 2022; Garbarova and Vartiak, 2022). Recently, South Asia is focusing on digital marketing activities and observing an evident growth in their economies and witnessing a rise in social media usage (Hawaldar et al , 2022).…”
Section: Research Contextmentioning
confidence: 99%